Asthma Phenotypes and Host Risk Factors Associated With Various Asthma-Related Outcomes in Health Workers - Mwanga, Hussein H.; Baatjies, Roslynn; Singh, Tanusha; Jeebhay, Mohamed F. (Frontiers in Allergy, 2021)
Work-related asthma phenotypes in health workers (HWs) exposed to cleaning agents have not been investigated extensively as other occupational exposures. This study aimed to describe asthma phenotypes and to identify important host risk factors associated with various asthma-related outcomes. A cross-sectional study of 699 HWs was conducted in two large tertiary hospitals. A total of 697 HWs completed questionnaire interviews. Sera collected from 682 HWs were analyzed for atopy (Phadiatop) and IgE to occupational allergens (NRL - Hev b5, Hev b6.02; chlorhexidine and ortho-phthalaldehyde - OPA). Methacholine (MCT), bronchodilator challenge (BDR) and fractional exhaled nitric oxide (FeNO) were performed. An asthma symptom score used five asthma-related symptoms reported in the past 12 months. Current asthma was based on use of asthma medication or an asthma attack or being woken up by an attack of shortness of breath in the past 12 months. Nonspecific bronchial hyperresponsiveness (NSBH) was defined as having either a positive MCT or a significant bronchodilator response. Two continuous indices of NSBH (continuous index of responsiveness (CIR) and dose-response slope (DRS)) were calculated. The prevalence of current asthma was 10%, atopic asthma (6%) and non-atopic asthma (4%). Overall, 2% of subjects had work-related asthma. There was a weak positive association between NSBH and FeNO (CIR: Beta coefficient (β) = 0.12; CI: 0.03 – 0.22 and DRS: β = 0.07; CI: 0.03 – 0.12). Combining FeNO ≥ 50 ppb with a BDR (mean ratio (MR) = 5.89; CI: 1.02 – 34.14) or with NSBH (MR = 4.62; CI: 1.16 – 18.46) correlated better with asthma symptom score than FeNO alone (MR = 2.23; CI: 1.30 – 3.85). HWs with current asthma were twice as likely to be atopic. FeNO was positively associated with atopy (OR = 3.19; CI: 1.59 – 6.39) but negatively associated with smoking status (GMR = 0.76; CI: 0.62 – 0.94). Most HWs sensitized to occupational allergens were atopic. Atopic asthma was more prevalent than non-atopic asthma. Most asthma-related outcomes were positively associated with allergic predictors suggesting a dominant role for IgE mechanisms for work-related symptoms and asthma associated with sensitization to OPA or chlorhexidine.